Does Technology Reduce or Amplify Financial Stress? A Cognitive-Behavioral Perspective on Nigerian Postgraduate Students - Jamila Yusuf; Hameed Olalekan Bolaji; Mustapha Shina Ahmed; Habibat Bolanle Abdulkareem (Universitas Pendidikan Ganesha, 2025)
Financial stress among postgraduate students has become an increasing concern in the digital era, particularly with the rapid adoption of digital financial tools that may both alleviate and intensify psychological distress. This study aims to examine whether technology reduces or amplifies financial stress among Nigerian postgraduate students through a cognitive-behavioral perspective. The study employed a conceptual and analytical research design using a qualitative, theory-driven approach grounded in Cognitive-Behavioral Theory (CBT). Data were collected from secondary sources, including approximately 70 peer-reviewed journal articles, policy documents, and empirical studies published between 2015 and 2024, retrieved from Scopus, Web of Science, Google Scholar, and JSTOR. Data analysis was conducted using thematic and comparative analysis, followed by theory-driven interpretation based on CBT principles. The findings indicate that digital financial technologies play a dual role. On one hand, tools such as budgeting applications, mobile banking, and online savings platforms enhance financial awareness, self-efficacy, and emotional regulation. On the other hand, misuse of fintech services, impulsive digital borrowing, exposure to fraud, and information overload trigger cognitive distortions that exacerbate anxiety and maladaptive financial behaviors. The results highlight that financial stress is shaped more by students’ cognitive interpretations and coping strategies than by technology itself. It is concluded that digital financial tools can reduce financial stress only when accompanied by adequate cognitive-behavioral skills and financial literacy.